Comparative international accounting - Nobes, Christopher
This edition takes a comprehensive look at the international dimensions of financial accounting and reporting. It offers overviews supported by information on countries and companies, examination of the requirements of International Financial Reporting Standards and of US GAAP, and studies of accounting in Japan and China.